O princípio da transparência na atividade financeira do estado - D'Almeida, José Fernando Costa (2005)
The purpose of the present work is demonstrate the constitutional principie of the transparency, as a instrument for solution of the financial crisis of the State. The discussion involves the study of the evolution of the State, concerning the financial aspects, and the social and economic factors of the contemporary world that have repercussion in the public finances, represented by the globalization, corruption and money laundering. There are still appreciated important subjects related with the theme, such as accountability, budget made with the participation of the citizens, budgets publicity, credit operations and revenues renouncements. There is examined. as a counterpoint, the transparency of taxpayefs conduct and its influence in public finances, standing out themes as privacy of bank information and tax elision. There is also demonstrated the international experience involving transparency. Finally, there are exposed the problems concerning to public finances in Brazil and the actions developed by government and no-government organizations aimed on transparency in the financial activity of the Brazilian State.